BATIK FRAKTAL: PERKEMBANGAN APLIKASI GEOMETRI FRAKTAL - Yulia Romadiastri (Universitas Pekalongan, 2013)
Fractal geometry is a branch of mathematics that studies of fractal shapes. Fractals are shapes that look irregular but are actually more closely if there is a pattern observed regularity in it. Fractals have infinite detail and can have a structure of selfsimilarity at different magnification levels. In many forms, it can be obtained by repeating the fractal pattern to infinity times. The development of fractal geometry itself has been found in a variety of fields, one of which is the making of batik pattern which is typical of Indonesian culture. unique and beautiful batik patterns can be obtained From this fractal forms. This of course can also enrich the culture of Indonesia.